Identification of Type VI Collagen Synthesizing Cells in Human Diabetic Glomerulosclerosis Using Renal Biopsy Sections - Mohammed Shawkat Razzaque; Takehiko Koji; Takashi Harada; Takashi Taguchi (Analytical Cellular Pathology)
Although the role of extracellular matrices in the development of glomerulosclerosis has been discussed widely, the cellular origin of type VI collagen in diabetic nephropathy (DN) has remained relatively unexplored. This study reports the distribution and cellular origin of type VI collagen in DN. Type VI collagen‐specific oligonucleotide probes and monoclonal antibody were used to assess the relative expression of mRNA for α1 (VI) chain and its translated protein in paraffin‐embedded renal biopsy sections of DN. By immunohistochemistry, compared to the control, increased deposition of type VI collagen was noted in the diffuse and nodular lesions of diabetic glomeruli. For cellular localization of type VI collagen mRNA, paraffin‐embedded renal sections of the control and DN were hybridized in situ with digoxigenin (Dig)‐labeled antisense oligo‐DNA probe complementary to a part of α1 (VI) mRNA. In comparison to the control kidney sections, increased numbers of intraglomerular cells (both mesangial and epithelial cells) were positive for α1 (VI) mRNA in renal biopsy sections of DN. From the results, we conclude that overexpression of type VI collagen by intraglomerular cells with its increased deposition might significantly contribute to the glomerulosclerosis found in DN.